Hilos Hilos de la memoria de Luis Felipe Chaves Martínez (2021)
The human being has the gift and the ability to tell stories, in doing so events of the past are spun, the narrative is woven and memory is made visible. This identifies the community, orality and writing that have long been the most common means of communication. This fabric was established as a narrative tool to communicate the generational memory in many families that keep the culture alive. It is thanks to weaving that today events from antiquity are known, which, if they had not been captured between the threads, would have been lost with the passing of generations, the decline of orality and the death of traditions.